2020
DOI: 10.1002/cpt.2071
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol and Abnormal Liver Chemistries in Healthy Adults: Results of a Phase I Clinical Trial

Abstract: Liver safety concerns were raised in randomized controlled trials of cannabidiol (CBD) in patients with Lennox-Gastaut and Dravet syndromes but the relevance of these concerns to healthy adults consuming CBD is unclear. The objective of this manuscript is to report on liver safety findings from healthy adults who received therapeutic daily doses of CBD for ~3.5 weeks and to investigate any correlation between transaminase elevations and baseline characteristics, pharmacogenetic, and pharmacokinetic data. Sixte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 23 publications
0
54
2
2
Order By: Relevance
“…The abnormal liver chemistry findings in this and other healthy volunteer and patient trials with CBD are described in more detail in a separate publication. 20 The authors of that publication concluded that healthy adults consuming CBD may experience elevations in serum ALT consistent with drug‐induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal liver chemistry findings in this and other healthy volunteer and patient trials with CBD are described in more detail in a separate publication. 20 The authors of that publication concluded that healthy adults consuming CBD may experience elevations in serum ALT consistent with drug‐induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that at doses below 1500 mg of CBD, the drug does not produce hedonic effects or cognitive impairment (Birnbaum, 2019). Nevertheless, these high CBD doses may be associated with a few side effects; including gastrointestinal, sedation and -most importantly -there is increasing evidence that sustained high doses of CBD may result in transaminase elevations which may represent drug-induced liver injury (Brown and Winterstein, 2019;Watkins et al, 2020).…”
Section: Initiating a Medical Cannabis Adjunct Trialmentioning
confidence: 99%
“…Finally, one area of significant controversy pertaining to the potential health benefits of CBD relates to the liver [ 23 ]. While some studies have suggested that CBD may promote favorable liver function, and may even be included in comprehensive treatments for liver diseases [ 24 ], others have suggested that CBD may harm the liver [ 25 ]. An additional goal of the current study was to determine the acute influence of a variety of different CBD formulations on circulating markers of liver function, and to determine if CBD availability (i.e., circulating concentration) predicts the magnitude and change of these circulating markers.…”
Section: Introductionmentioning
confidence: 99%